Psychological distress among primary school teachers: a comparison with clinical and population samples. (January 2019) - Titheradge, D.; Hayes, R.; Longdon, B.; Allen, K.; Price, A.; Hansford, L.; Nye, E.; Ukoumunne, O.C.; Byford, S.; Norwich, B.; Fletcher, M.; Logan, S.; et al.
Abstract: Objectives: This analysis explored the level of psychological distress among primary school teachers in the South West of England as compared with clinical and general population samples. Study design: Secondary analysis of data from the Supporting Teachers and Children in Schools (STARS) trial completed by up to 90 teachers at baseline, 9, 18 and 30 months of follow-up. Methods: We used the Everyday Feelings Questionnaire (EFQ) as a measure of psychological distress. Baseline data on teachers were compared with a population sample of professionals and a clinical sample of patients attending a depression clinic. Results: Our teacher cohort experienced higher levels of psychological distress than comparable professionals from the general population, which were sustained over 30 months of follow-up. Levels of psychological distress were lower than those found in the clinical sample. Using a cut-point indicative of moderate depression, our data suggest that between 19% and 29% of teachers experienced clinically significant distress at each time-point. Conclusions: We detected high and sustained levels of psychological distress among primary school teachers, which suggests an urgent need for intervention. Effective support for teachers' mental health is particularly important given the potential impact of poor teacher mental health on pupil well-being, pupil attainment and teacher–pupil relationships. Highlights: Primary school teachers experience high levels of psychological distress. More than a fifth of teachers were experiencing distress at a clinically significant level. These findings were sustained for 10% of the sample from the baseline over 30 months follow-up. Older teachers experienced higher levels of clinically significant distress.